2002
DOI: 10.2320/matertrans.43.920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Addition on Shape Memory Characteristics of Fe-Mn-Si-Cr Alloy

Abstract: Nitrogen-microalloying and partial substitution of Cr for Mn have been employed to enhance the shape memory effect and corrosion resistance of Fe-Mn-Si based alloys. Typically, the tested alloys with nominal composition Fe-25Mn-6Si-5Cr-(0.12-0.14)N in mass% exhibit perfect shape recovery for a 3% pre-strain after only one cycle of thermomechanical training. The related mechanism has been discussed, taking account of the effect of nitrogen on the stacking fault energy (SFE) or the stacking fault probability (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…<0.25 wt%, reduces P sf [36]. However, our results [37] also showed that nitrogen-microalloying, even with very small amount, definitely improves SME. This is because of its strong strengthening effect on the parent phase, overwhelming its negative effect on P sf and playing a key role in getting a high recoverable strain.…”
Section: The Prediction Of Smecontrasting
confidence: 69%
See 1 more Smart Citation
“…<0.25 wt%, reduces P sf [36]. However, our results [37] also showed that nitrogen-microalloying, even with very small amount, definitely improves SME. This is because of its strong strengthening effect on the parent phase, overwhelming its negative effect on P sf and playing a key role in getting a high recoverable strain.…”
Section: The Prediction Of Smecontrasting
confidence: 69%
“…An increase in the yield strength resulting in the retardation of dislocation slip is proposed as the explanation of the carbon effect [38]. Wan et al [37] found that typically a tested alloy with nominal composition Fe-25Mn-6Si-5Cr-0.14N in wt% exhibits perfect shape recovery for a 3% pre-strain after only one cycle of thermo-mechanical training, as seen in Fig. 9.…”
Section: Microalloyingmentioning
confidence: 95%
“…Karaman et al [20] and Gavriljuk et al [21] found that, in a Fe-24Mn-6Si-5Cr shape memory alloy, the ISFE increased when N was added up to 0.4 mass pct. Wan et al [22] calculated that the ISFE increases when maximum 0.25 mass pct of N is added.…”
Section: Introductionmentioning
confidence: 99%
“…Since Sato et al found in 1982 that Fe-30Mn-6Si alloys exhibited an excellent shape memory effect in a single crystal [1], extensive studies have been carried out on this alloy and its modification [2][3][4][5]. The shape memory effect of iron-based shape memory alloys is based on a stress induced martensite transformation (c!e transformation) by the extension and contraction of stacking faults.…”
Section: Introductionmentioning
confidence: 99%
“…The shape memory effect of iron-based shape memory alloys is based on a stress induced martensite transformation (c!e transformation) by the extension and contraction of stacking faults. When the martensite transformation temperature M s is just a little higher than room temperature, the stress-induced c!e transformation easily occurs with only a small mechanical driving force that is equal to the ratio of the stacking fault energy of austenite (E sf ) to the energy associated with Shockley partials [1][2][3]. According to the composition design to obtain a good shape memory effect [6][7][8][9], it was found that the alloy having the lowest stacking fault energy and single austenite phase has the best shape memory effect.…”
Section: Introductionmentioning
confidence: 99%